Analysis of circular polarization backscattering and target decomposition using gb-sar - Izumi Y.; Demirci S.; Baharuddin M.Z.; Sumantyo J.T.S.; Yang H. (Electromagnetics Academy, 2023)
Calibration; Circular polarization; Matrix algebra; Polarimeters; Polarization; Experimental verification; Full polarimetric synthetic aperture radar (SAR); Laboratory environment; Polarimetric analysis; Received signal strength; Scattering matrices; Scattering mechanisms; Target decomposition; Synthetic aperture radar